(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2022)
The Athenian nautodikai are mostly mentioned in fragmentary sources (a hint in IG I3 41; evidence of their activity in a couple of verses from the old comedy and in a fragment from the Macedonian Craterus) and in lexicographers. The earliest records date from the 440s BCE, and they initially seem to have jurisdiction over cases related to ascertaining citizenship (graphai xenias), at least until the last decades of the V century BCE. By the early years of the IV century BCE the nautodikai change function: they are mentioned in the Lysian oration On the property of Eraton as judges engaged in cases concerning emporoi. This function is also confirmed by lexicographers. By reviewing all the evidence related to this officials, the article aims at showing how a constant feature of the nautodikai is that of urgency and simultaneously of default in the conduct of cases. Their limited functionality as a panel of judges would explain the abolition of their office at the latest around the middle of the IV century BCE, when the need to ensure a rapid solving of the cases was especially felt, particularly in the regulation of commercial disputes.